Direct and Indirect Selection for Grain Yield and Grain Weight in Late Generations of Bread Wheat under Drought Stress and Normal Irrigation Environments - Rasha E. Mahdy; Dikhnah Ashehri; Hanan Ali Alatawi; Hadba Al-Amrah; Ezzat E. Mahdy (Plants, 2022)
Two cycles of pedigree selection for grain yield/plant (GY/P) and grain weight (GW) (100-grain weight) were imposed under drought stress and normal irrigation to study the direct and indirect selection of GY/P and GW in bread wheat. The selection started in the F6-generation (Cycle0-C0) of bread wheat (Triticum aestivum L.) traced back to the cross (Giza 164/Sids 4) of two Egyptian cultivars. The narrow sense heritability was higher under drought than under normal irrigation and increased by selection. Under drought, the observed direct gain after two cycles of selection for GW was 21.51% (p ≤ 0.01), and accompanied with an indirect gain in GY/P of 15.52%. The observed direct gain for GY/P was 17.98% and the indirect gain in GW was 13.81%. Under normal irrigation, the observed direct gain for GW was 12.86% and the indirect gain for GY/P was 16.04%. The direct gain in GY/P was 16.04% and the indirect gain in GW was 11.95%. The genotypic correlations were different in both environments before and after selection. Single trait selection was effective in improving the selection criterion, and selection greatly affected gene associations.